THE INFLUENCE OF DIGITAL MARKETING, QUALITY PRODUCT, AND BRAND IMAGE ON PURCHASING DECISIONS OF SARI ROTI AMONG STUDENTS OF MUHAMMADIYAH UNIVERSITY OF JEMBER - Wati, Agustina Setyo; Eko Budi Satoto; Rusdiyanto, Rusdiyanto (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The aim of this research is to identify and analyze the influence of digital marketing, product quality, and brand image on purchasing decisions for Sari Roti among Muhammadiyah University Jember students. By understanding these factors, it is hoped that it can contribute to the development of a more effective marketing strategy for Sari Roti, as well as providing a better understanding of student consumer behavior. The targets to be achieved in this research are to contribute new knowledge in the field of marketing, especially regarding the factors that influence purchasing decisions for snack products among students, provide recommendations to the Sari Roti company regarding more effective marketing strategies to increase sales of its products, especially students, and test and develop existing theories related to the influence of marketing variables on consumer behavior. Method: This research uses quantitative research with a causal approach to test the independent variables (digital marketing, product quality, and brand image) against the dependent variable (purchasing decisions). The causal approach was chosen because it aims to determine the causal relationship between these variables. Data was collected through questionnaires distributed to 300 respondents. The data analysis technique used is multiple linear regression. Results: The research results show that digital marketing does not have a significant effect on purchasing decisions, product quality does not have a significant effect on purchasing decisions, and brand image has a significant effect on purchasing decisions. Novelty: This research provides new insights into the effectiveness of marketing strategies for snack products among students, particularly in understanding the limited impact of digital marketing and product quality while emphasizing the role of brand image in purchasing decisions.